Estudos dos efeitos da implantação de uma usina hidrelétrica sobre comunidades de mamíferos do cerrado - Marcos Martins Silva (2014)
The water potential of Brazil makes it possible to meet an increased demand for hydroelectric power plants to supply the high energy needs associated to the development of the country. The construction of dams brings significant changes in the landscape and loss of habitats. The present study aimed to analyze the impacts of the construction of the Serra da Mesa Hydroelectric / GO, located in the savanna domain, over a community of non-flying small mammals. The capture-recapture methodology for the identification and collection of the richness and diversity was used in four areas, three of which went to the status of islands after flooding and one that was not affected by dam as control area. We analyzed data from the Jackknife estimator and the Shannon index, concluding that the implementation of the reservoir caused the change in the dynamics of mammalian community, with a reduction of habitat and species loss.